Minimally Invasive Mitral Valve Surgery: A Systematic Review - Lucà, Fabiana (Hindawi Publishing Corporation, 2013)
In the recent years minimally invasive mitral valve surgery (MIMVS) has become a well-established and increasingly used option for managing patients with a mitral valve pathology. Nonetheless, whether the purported benefits of MIMVS translate into clinically important outcomes remains controversial. Therefore, in this paper we provide an overview of MIMVS and discuss results, morbidity, mortality, and quality of life following mitral minimally invasive procedures. MIMVS has been proven to be a feasible alternative to the conventional full sternotomy approach with low perioperative morbidity and short-term mortality. Reported benefits of MIMVS include also decreased postoperative pain, improved postoperative respiratory function, reduced surgical trauma, and greater patient satisfaction. Finally, compared to standard surgery, MIMVS demonstrated comparable efficacy across a range of long-term efficacy measures such as freedom from reoperation and long-term survival.